O CURRÍCULO DE REFERÊNCIA DO ESTADO DE MATO GROSSO DO SUL NO OLHAR DOS(AS) COORDENADORES(AS) PEDAGÓGICOS DA REDE ESTADUAL DE ENSINO EM TRÊS LAGOAS, MS: ELABORAÇÃO E DESENVOLVIMENTO. - Ana Flávia Miranda Martins (2022)
The present work analyzed the elaboration and development of Mato Grosso do Sul Reference Curriculum Elementary School implemented in 2019 at state schools, under the supervision of State Education Network’s educational coordinators in the city of Três Lagoas, it also had intention to identify the participation of the schools and investigated people in the curriculum document’s elaboration process; to analyze the elaboration process; to understand the educational coordinator’s continued formation process; and to identify the continuities and ruptures between the National Curriculum Regular Basis (BNCC) and the Mato Grosso do Sul Reference Curriculum. The research is a qualitative approach (BOGDAN; BIKLEN, 2013), from the Dialectic-historical materialism’s assumption (MARX, 2013). The theoretical line adopted to support the arguments related to curriculum and scholar relationships was the historical-critical (SAVIANI, 2019). In this work, the discussions were built based on the Gramscian Integral State concept (2002, 2004, 2007). The discussions about curriculum also relied on others ideas: Apple (2008); Chizzotti; Ponce, (2012); Saviani (2012, 2015, 2016, 2019); Libâneo (1992, 1994, 2013); Arroyo (1982, 2013); Duarte (2018). To discuss Public Policies inside the educational context, support was obtained in Lopes (2006, 2018); Marx (2008); Rodriguéz (2010); Mészáros (2011); Macedo (2016, 2018); among others. The unfolding of the research took place in three stages: the first one consisted in the bibliographic and documentary survey, in that way, it was examined through the realization of previous knowledge state about indexation bases of scientific works, being them: (Scielo.br, Scholar Google, Banco de Teses e Dissertações da CAPES, and Biblioteca Digital de Teses e Dissertações), it was found that there were no works with the same investigative theme. In the documentary survey were consulted Curriculum documents prior to CRMSEF, Resoluções e Decretos do Estado de MS which deal with pedagogical coordination activities, the CRMSEF itself, certificates issued by the Secretaria de Estado de Educação de Mato Grosso do Sul (SED/MS), and the BNCC. The second stage consisted in carrying out semi-structured interviews applied with the pedagogical of the state network in the municipality of Três Lagoas/MS in the early years of elementary schools. In the last stage were realized the collected information treatment in the field according to content analysis (BARDIN, 2016). The research results ratified that the CRMSEF was elaborated to attend the educational model proposed by the curriculum policies materialized in the BNCC, this document has a normative and centralizing nature. It was found that CRMSEF aligns to BNCC and there are small differences between the two documents. It was identified that there was no autonomy in the participation of school subjects in the construction of the curricular proposal, since few elements could be changed. In participant’s perception, CRMSEF has the function of enabling BNCC’s implementation. It was perceived that there are uncertainties by the educators in relation to the state curriculum proposal implementation when it comes to promoting equity, as the understanding about the document will certainly not be the same at all school units as all schools have their own particularities. It was concluded that CRMSEF, guided by BNCC’s, aligns with the educational policies designed by multilateral organizations, being developed in Brazil since 1990s, as expression of capitalism’s globalization, reinforcing the need to adjust resistances in the educational scope, something that can also happen through the pedagogical coordination actions. Keywords: Public Educational Policies; Mato Grosso do Sul Reference Curriculum; Elementary School; Pedagogical Coordinators.